2013
DOI: 10.1007/s00251-013-0679-8
|View full text |Cite|
|
Sign up to set email alerts
|

FCGR3A-158 polymorphism influences the biological response to infliximab in Crohn’s disease through affecting the ADCC activity

Abstract: An association between FCGR3A-158 V/F polymorphism and biological responses to infliximab has been reported in Crohn's disease (CD) in Western countries. However, little is known about the mechanism by which gene polymorphism affects the responses to infliximab. The aims of this study were to confirm the association in Japanese CD patients and to reveal the effect of gene polymorphism on biological responses to infliximab. Japanese CD patients were examined retrospectively at weeks 8 and 30. Clinical and biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 24 publications
5
60
1
Order By: Relevance
“…Other factors affecting the binding to FcgRIIA alleles are the size of the immunocomplexes [35] and possibly intramolecular interactions between the variable and the constant regions of the monoclonal antibody [38,39]. The three processes could be defective in the context of weak binding to FcgRIIA, as already demonstrated for ADCC and complement activation for weak binding to FcgRIIIA [41]. This led us to postulate that INX also binds differentially with the FcgRIIA alleles, whereas ETC and ADM are not affected.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Other factors affecting the binding to FcgRIIA alleles are the size of the immunocomplexes [35] and possibly intramolecular interactions between the variable and the constant regions of the monoclonal antibody [38,39]. The three processes could be defective in the context of weak binding to FcgRIIA, as already demonstrated for ADCC and complement activation for weak binding to FcgRIIIA [41]. This led us to postulate that INX also binds differentially with the FcgRIIA alleles, whereas ETC and ADM are not affected.…”
Section: Discussionmentioning
confidence: 79%
“…Glycosylation of therapeutic monoclonal antibodies depends on many factors: from the cell line used for their in-vitro production to multiple variables in the culture procedure [37]. Some of these functions could impinge in the efficacy of INX treatment, but previous work has focused on the cytotoxicity of INX on in- flammatory cells expressing membrane TNF [40,41]. Some of these monoclonal antibodies showed increased binding with the 131R allele relative to the H131 allele, whereas others showed decreased binding to the 131R allele [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…The authors also observed the same trend at week 2 . Similar results were found in another study by Moroi et al ., who found a significantly larger decrease of CRP (ΔCRP) and percentage decrease (ΔCRP%) among 12 TT genotype carriers than among 38 TG and 52 GG genotype carriers ( P = 0.001 and P = 0.044, respectively) at week 8 whereas no differences were found at week 30 and no differences were found in relation to the clinical response criteria . FCGR3A encodes a receptor for immunoglobulin G (IgG), Fc γ RIIIa.…”
Section: Resultsmentioning
confidence: 93%
“…30 Furthermore, in some rheumatoid arthritis patients, TNF blocking has shown to induce psoriasis, 31,32 clearly supporting the existence of very different pathogenic mechanisms. Recently, pharmacogenetic studies of FCGR2A and FCGR3A gene variants and anti-TNF therapy response have provided suggestive evidence for opposite genetic effects between rheumatoid arthritis and Crohn's disease, 33 rheumatoid arthritis and psoriatic arthritis 34 and even between rheumatoid arthritis and psoriasis. 20 Taken together, these results support the existence of different TNFrelated pathways and, consequently, different biologic mechanisms by which TNF blocking is an effective treatment.…”
Section: Discussionmentioning
confidence: 98%